TRACING ARABIC LANGUAGE ENTITIES IN THE QURAN
This article examined how the Qur’an talks about the Arabic used in it, its essence, existence, and urgency, departing from the dialectic of the foreign languages existence in the Qur’an. This study was literature research using an interpretive approach with the method maud